The educational experiences of students with Asperger Syndrome. (Kairaranga, 2004)
The Ministry of Education 3 policy, Special Education 2000 (SE 2000) was intended to promote a model that ensured all students received an education that involved successful experiences [Ministry of Education, 1996). Students with Asperger Syndrome (AS) often have difficulty adapting to and achieving these successful experiences in their educational environment. This paper summaries the findings from a research project that was designed to investigate the issues that arise for students with AS determine whether or not these experiences are generally positive or negative, and examine to what extent teachers have knowledge of AS Data was gathered from interviews with three students their parents and their teachers and a survey to examine teacher knowledge. Data was also gathered from nine interviews and twenty-nine questionnaires. This paper reports on the data gathered from the interviews. The emerging issues were: Difficulties accessing the curriculum, social difficulties misunderstanding of parents' roles, teacher responsibility, bullying lack of teacher aide support, placement difficulties and sensory and environmental factors. The study concluded that the educational experience of the students was generally negative. The level of teacher knowledge was low, although the majority of teachers expressed an interest in gaining further knowledge.